Study on the stability and accuracy of the new Booster portable cardiopulmonary function meter - Hezhang Yun; Hezhang Yun; Wenbo Zhang; Chen Yu; Chen Yu; Qiang Li; Yafeng Song (Frontiers in Physiology)
This study aims to assess the reliability and accuracy of a novel portable cardiopulmonary function meter, “Booster,” developed by our research group, across various exercise intensities and modalities. The study was segmented into reliability and validity assessments. Twenty-two male participants underwent reliability testing, conducting two sequential tests on a treadmill while wearing the Booster to measure VO2 and VE among other parameters at increasing intensities. For validity testing, 64 participants were randomly divided into treadmill and cycle ergometer groups, with tests conducted using both the Booster and the Cortex Metalyzer 3B systems. Overall, the Booster demonstrated high retest reliability for VO2 and VE measurements during treadmill exercises, albeit showing poor consistency during rest and low-intensity exercise phases. Validity testing indicated no significant differences in VO2 and VE measurements between Booster and Cortex Metalyzer 3B across all exercise stages on both treadmill and cycle ergometer, suggesting good correlation. However, discrepancies in measurements between Booster and Cortex Metalyzer 3B were observed during rest and maximal exertion phases. The Booster exhibits commendable reliability and stability during most treadmill exercise phases and shows generally acceptable validity compared to the Cortex Metalyzer 3B system. Nonetheless, potential measurement discrepancies may occur during rest and maximal exertion conditions.